PENGARUH JARAK TANAM DAN JUMLAH BIBIT PERLUBANG TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH ASAL BIJI ( True Shallod Sheed ): Bawang Merah, Jarak Tanam, Jumlah Bibit - Ahmad Asrori; Priyono, Priyono; Triyono, Kharis (innofarm, 2023)
Influence distance plant and the number of seeds onthe growth and yield of shallot (Allium ascalonicumL.). This research is Research This aim For know There’s nope interaction between distance plant amount seeds per hole to growth And results onion red origin seed (True Shallow Seed) . The research location will be carriedout in Bangsri Village. Karangpandan District. Karanganyar Regency, Central Java with analtitude of 305 meters abov sea. level and types land latosol . Conducting research in November 2022 - February 202 3. This is study used 3 x 3 factorials Completely RandomizedBlockDesign with3 replications. The first factor studied was the spacings consisting of 3 levels, namely 20 cm x10 cm, 20 cm x 20 cm, and 20 cm x 25 cm. The second factor is the number of seeds consisting of 3 levels, namely 1.2 and 3 seed perplanting hole.Results study showing thats distance plant give influence on high parameters plant weight tubers wet per clump, weight hasty wet, heavy tubers dry per plot. and No give influence on amount leaves, number tubers thick, heavy tubers dry per clump, by weight hasty dry, and tuber diameter . Total seeds per hole give influence to amount leaves, number tubers per hill, weight hasty wet, heavy tubers wet, heavy tubers dry per plot, and No influential on tall plant weight tubers dry per clump, by weight hasty dry, and tuber diameter . Interaction distance crop (J) and amount seeds per well (B) no give influential to all the parameters are meters.